Coreless fiber refractive index sensor in terms of intensity sensing and wavelength shift (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
A multimode no core fiber (NCF) -based refractive index interferometric (RI) sensor has been demonstrated through experiment. Coreless fibers are directly exposed to environmental factors. The output spectrum changes with the refractive index, type, and contraction of the ambient medium such as Magnesium permanganate. The MachZehnder optical fiber sensor had a 523 nm/RIU sensitivity, and when graphene oxide was coated on top of the gold layer, the sensitivity rose to 950 nm/RIU. Either optical density contrast or wavelength shifting was used to achieve this increase in sensitivity. Coreless fiber is a weakly oriented multi-mode fiber with an index profile when the environment around the sensor is lower than that of a non-core fiber that has single-mode fibers that are spliced at both ends of the coreless fiber segment. As a result, it takes on the shape of the classic (SM-MM-SM) fiber structure but is bigger.